2023
DOI: 10.1002/adfm.202301425
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Ionic Behavior with Bifunctional Additives for Efficient Sky‐Blue Perovskite Light‐Emitting Diodes

Abstract: Perovskite Light-emitting diodes (PeLEDs) have emerged as a promising technique for future high-definition displays due to their outstanding electroluminescent characters. However, the development of blue PeLEDs toward practical applications is seriously hindered by their inferior performance, which mainly arises from the detrimental halide ionic behavior and thus severe nonradiative recombination in mixed-halide blue perovskite materials. Herein, efficient sky-blue PeLEDs featuring spectrally stable emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 41 publications
0
42
0
Order By: Relevance
“…Halide perovskite-based light-emitting diodes (PeLEDs) are considered promising candidates for the next generation of solid-state displays due to perovskite’s optoelectronic properties, such as tunable band gap, high photoluminescence quantum yield (PLQY), and excellent color purity. The state-of-the-art external quantum efficiency (EQE) of green and red PeLEDs have, respectively, reached 28.1% and 25.8%, and that of sky-blue devices has reached 18.65%. For PeLEDs to be successfully commercialized in displays, a highly efficient device emitting saturated blue color is essential. However, the efficiency of deep-blue emitting PeLEDs still lags behind.…”
Section: Introductionmentioning
confidence: 99%
“…Halide perovskite-based light-emitting diodes (PeLEDs) are considered promising candidates for the next generation of solid-state displays due to perovskite’s optoelectronic properties, such as tunable band gap, high photoluminescence quantum yield (PLQY), and excellent color purity. The state-of-the-art external quantum efficiency (EQE) of green and red PeLEDs have, respectively, reached 28.1% and 25.8%, and that of sky-blue devices has reached 18.65%. For PeLEDs to be successfully commercialized in displays, a highly efficient device emitting saturated blue color is essential. However, the efficiency of deep-blue emitting PeLEDs still lags behind.…”
Section: Introductionmentioning
confidence: 99%
“…32 Similarly, in Figure 2c, the dominant peaks of I 3d 3/2 and I 3d 5/2 shift from 619.1 and 630.59 eV to the high binding energy of 619.17 and 630.67 eV after the KTFA modification, owing to the ionic bonding between K + and iodide ions. 30 Figure 2d shows that trifluoroacetate's (TFA's) C�O bond stretching vibration shifts from 1688 cm −1 to a lower wavenumber of 1677 cm −1 in the KTFA and PbI 2 mixture owing to the interaction between the C�O and Pb 2+ ions. 32 Moreover, the N−H stretching vibration peak of POEAI, located at 3468 cm −1 , shifts to 3430 cm −1 in the KTFA and POEAI mixture, which is attributed to the intermolecular interaction of hydrogen bonding between F atoms and N−H (Figure 2e).…”
mentioning
confidence: 99%
“…We use triexponential decay functions to fit the TRPL curves. 30,34 The parameters extracted from the fitted curves are summarized in Table S2 (Supporting Information). τ 1 is the fast decay time constant, which is related to nonradiative recombination caused by defects, while τ 2 and τ 3 represent the slow decay time constant, which is associated with radiative recombination.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, there are two strategies to achieve blue perovskite emitters: Reducing the size of bulk perovskites to exciton Bohr radius and introducing chloride into perovskites to expand their bandgaps. , Unfortunately, the low-dimensional perovskites are in a dilemma over how to improve the poor electronic properties induced by the excess large-size organic cations or ligands. Meanwhile, the mixed chloride/bromide perovskites confront the challenges of low photoluminescence quantum yields (PLQYs) and poor spectra stability resulting from the chloride vacancy defects and resultant halide ion migration under electric field. , Therefore, it is critical to suppress the defect formation in perovskite films, including halide vacancy, uncoordinated Pb 2+ ions, etc. For example, Karlsson et al demonstrated a vapor-assisted crystallization technique that can effectively suppress the ion migration in mixed-halide blue PeLEDs . Xu et al investigated the passivation effect of phosphine oxide additive in different antisolvents, in which PO groups could reduce the defect density effectively, thus resulting in an EQE of 9.5% at 488 nm .…”
mentioning
confidence: 99%